Genome-wide identification of sucrose non-fermenting-1-related protein kinase genes in maize and their responses to abiotic stresses - Feng, Xue; Meng, Quan; Zeng, Jianbin; Yu, Qian; Xu, Dengan; Dai, Xuehuan; Ge, Lei; Ma, Wujun; Liu, Wenxing (Frontiers in Plant Science, 2022)
Protein kinases regulated signal transduction play an important role in plants responding to environmental changes. As a large family of protein kinases, sucrose non-fermenting 1 (SNF1)-related protein kinase (SnRK) were found and functional verified in many plants. Nevertheless, little has been known in SnRK family of Zea mays. Totally, 60 SnRK genes located on 10 chromosomes were discovered in maize. On the basis of phylogenetic and conserved motif analyses, ZmSnRKs were classified into three subfamilies (ZmSnRK1, ZmSnRK2, ZmSnRK3), consist of 4, 14 and 42 genes, respectively. Gene structure analysis showed that 33 of the 42 ZmSnRK3 genes contained only one exon. Most ZmSnRK genes contained at least one ABRE, MBS and LTR cis-elements responding to abiotic stresses in their promoter regions and a few ZmSnRK genes had AuxRR-core, P-box, MBSI and SARE cis-elements. The Ka/Ks ratio of 22 paralogous ZmSnRK gene pairs revealed that the ZmSnRK genes family had experienced a purifying selection. Meanwhile, we analyzed the expression profiles of ZmSnRKs and they exhibited significant differences in various tissues and abiotic stresses. In addition, regulatory network of ZmSnRKs were constructed through protein interactions and miRNA targeted gene prediction. A total of eight ZmPP2Cs which can interact with ZmSnRK proteins and forty-six miRNAs which can target 24 ZmSnRKs were identified. Generally, these results provide valuable information for further function verification of ZmSnRKs, and helps to better comprehend the role of ZmSnRKs in climate-resilience of maize.